Improving Energy-Saving Competencies: Needs Analysis and Training Program Design for Islamic School Teachers - Rohmatulloh, Rohmatulloh; Rohman, Asep; Rosenda, Diden; Nadia, Matsna Afwi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
AbstractTeachers need to be more competent in understanding and implementing the value of energy-saving ethics, which affects the process of instilling its value in students. In fact, there are many subjects in Indonesia's national and religious education curriculum that contain the value of energy-saving ethics. The purpose of this research is to design a training and competency development program for Islamic school (madrasah) teachers integrated with the boarding school system (pesantren). The design stages included needs analysis, textbook analysis for Islamic Religious Education, Science, and Language in grades VII-IX, competency analysis, and curriculum and syllabus design. At each stage, we conducted interviews with Islamic Religious Education teachers, energy conservation instructor, curriculum development experts, and linguists. We also carry out benchmarking based on the curriculum and syllabus documents developed by training institutions. The research results led us to design a training program that emphasizes the ability to internalize religious ethical value messages related to energy-saving learning. The implementation uses a place-based education approach and a blended learning format that is highly flexible in terms of resource availability for teachers and schools. We discuss the implications of the research results, emphasize the use of local green energy issues and resources as learning resources, and establish partnerships with universities and human resource development institutions, as well as local teacher learning communities in the energy field.AbstrakGuru harus lebih kompeten dalam memahami dan menerapkan nilai etika hemat energi sehingga memberikan dampak pada proses penanaman nilai tersebut kepada peserta didik. Faktanya, banyak mata pelajaran dalam kurikulum pendidikan nasional dan agama di Indonesia yang mengandung nilai etika hemat energi. Tujuan penelitian ini adalah desain program pelatihan dan pengembangan kompetensi guru sekolah Islam atau madrasah yang terintegrasi dengan sistem pondok pesantren. Tahapan desain meliputi analisis kebutuhan, analisis buku teks pelajaran Pendidikan Agama Islam, sains, dan bahasa kelas VII-IX, analisis kompetensi, serta desain kurikulum dan silabus. Pada setiap tahap, wawancara dilakukan dengan guru sekolah, instruktur konservasi energi, ahli pengembangan kurikulum, dan ahli bahasa. Benchmarking dilakukan juga berdasarkan dokumen kurikulum dan silabus yang dikembangkan oleh lembaga pelatihan. Hasil penelitian mengarahkan kami untuk mendesain program pelatihan yang menekankan pada kemampuan internalisasi pesan nilai etika agama terkait pembelajaran hemat energi. Penerapannya menggunakan pendekatan place-based education dan format blended learning yang sangat fleksibel dalam hal ketersediaan sumber daya bagi guru dan sekolah. Kami membahas implikasi hasil penelitian, menekankan pada penggunaan isu dan sumber daya energi hijau lokal sebagai sumber belajar, dan menjalin kemitraan dengan perguruan tinggi dan lembaga pengembangan sumber daya manusia, serta komunitas belajar guru lokal di bidang energi. How to Cite: Rohmatulloh, Rohman, A., Rosenda, D., & Nadia, M. A. (2024). Improving Energy-Saving Competencies: Needs Analysis and Training Program Design for Islamic School Teachers. TARBIYA: Journal of Education in Muslim Society, 11(1), 47-64. doi:10.15408/tjems.v11i1.40160.